2017
DOI: 10.1039/c6cc10321a
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable chemisorption of dyes with pyridyl anchors over TiO2: application in dye-sensitized photoelectrochemical water reduction in aqueous media

Abstract: A polypyridyl ruthenium sensitizer possessing pyridyl anchors (Ru-py) forms much stronger chemical linkages to TiO surfaces compared to the conventional carboxylate and phosphonate ones. A highly stable dye-sensitized photoelectrochemical cell for water reduction is successfully demonstrated using this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…In the literature, catalysis with pyridine as an anchor for surface-bound catalysts is scarcely reported. Sakai and Ozawa et al 20 have constructed a photoanode with a pyridine-functionalized [Ru (bpy) 3 ] 2+ (bpy = 2,2′-bipyridine) complex as the chromophore immobilized on TiO 2 film. This photoanode was examined for the PEC oxidation of EDTA.…”
mentioning
confidence: 99%
“…In the literature, catalysis with pyridine as an anchor for surface-bound catalysts is scarcely reported. Sakai and Ozawa et al 20 have constructed a photoanode with a pyridine-functionalized [Ru (bpy) 3 ] 2+ (bpy = 2,2′-bipyridine) complex as the chromophore immobilized on TiO 2 film. This photoanode was examined for the PEC oxidation of EDTA.…”
mentioning
confidence: 99%
“…3) passing through the origin. A case opposite to the above, indicates different mass transfer rates in the initial and final stages of adsorption, indicating the involvement of film diffusion in addition to intra particle diffusion [33,34]. Figure 10d shows the linear fitting plot of intra particle diffusion model.…”
Section: Photocatalytic Experiments and Kinetic Analysismentioning
confidence: 92%
“…4 a, Q e were not found to be in good match which implied that adsorption kinetics cannot be well explained by pseudo second order adsorption model [32]. Pseudo second order model presents the chemisorption process which involves the formation of relatively strong bonds with the surfaces [33].…”
Section: Photocatalytic Experiments and Kinetic Analysismentioning
confidence: 92%
“…By contrast, hydroxamic acids and silatranes, which are less investigated, are more robust against hydrolysis and more stable over wider pH ranges (pH 2–11) 92. In addition to the groups mentioned above, Sakai and co‐workers have demonstrated that pyridine groups forming more stable surface links than the widely used carboxylic and phosphonic groups as an anchoring group on TiO 2 surfaces 114. Thiol groups are also good candidates for binding on sulfophilic metal containing photoelectrodes 41,48.…”
Section: Semiconductor/molecular Catalyst Interfacesmentioning
confidence: 99%